2004
DOI: 10.1089/acm.2004.10.1053
|View full text |Cite
|
Sign up to set email alerts
|

Quality, Labeling Accuracy, and Cost Comparison of Purified Soy Isoflavonoid Products

Abstract: There is a lack of uniformity among the products tested and the majority (67%) of the products contained less than 90% of labeled amounts. There is significant variability in the compositions between the products and in the composition of the same product over time. Consumers cannot trust isoflavonoid product labels to represent the product's content accurately or that product pricing is a reflection of isoflavone content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…Quantitative analysis of three main isofl avones (genistein, daidzein and glycitein), their glycosides as well as malonyl and acetyl derivatives was performed by using high performance liquid chromatography (HPLC) according to Chua et al (2004). At least three tablets of each product were tested separately, and standard deviation (SD) values were always lower than 1%.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative analysis of three main isofl avones (genistein, daidzein and glycitein), their glycosides as well as malonyl and acetyl derivatives was performed by using high performance liquid chromatography (HPLC) according to Chua et al (2004). At least three tablets of each product were tested separately, and standard deviation (SD) values were always lower than 1%.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, concentrations of formononetin and biochanin A should be the main determinants used to compare the isoflavone content differences between products. In our previous study of soy isoflavone supplement products, we noticed a lot of peaks other than soy isoflavone's peaks in 13 products that were analyzed and classified them as impurities 13 . In our analysis of 5 red clover products and the USP red clover standard extract, peaks resulting from these impurities (i.e., peaks other than biochanin A, formononetin, genistein and daidzein) are more prevalent in the chromatograph profiles of red clover products than from the standard USP red clover extract ( Fig.…”
Section: Hplc and Uplc Profiles Of Various Red Clover Productsmentioning
confidence: 99%
“…In a previous study from our laboratory, a comparison among thirteen different retailed soy isoflavone products showed that the exact compositions of these products varied drastically from product to product 13 . Only four out of 13 products contained 90% or more of the isoflavone contents claimed on the label.…”
Section: Introductionmentioning
confidence: 99%
“…The level of impurities was high in most of the products. Chua et al [15] found that among 13 commercially available extracts (purchased in the Washington State, USA), only 4 contained at least 90% of the isoflavone content claimed on the label. Moreover, in 2 products, impurities exceeded 40% of the total mass of the extract.…”
Section: P<005 (Values Marked With Asterisks)mentioning
confidence: 99%